Comparison of the Immunogenicity of Cell Culture-Based and Recombinant Quadrivalent Influenza Vaccines to Conventional Egg-Based Quadrivalent Influenza Vaccines Among Healthcare Personnel Aged 18–64 Years: A Randomized Open-Label Trial. (10th July 2021) - Dawood, Fatimah S; Naleway, Allison L; Flannery, Brendan; Levine, Min Z; Murthy, Kempapura; Sambhara, Suryaprakash; Gangappa, Shivaprakash; Edwards, Laura; Ball, Sarah; Grant, Lauren; Belongia, Edward; Bounds, Kelsey; et al.
Abstract: Background: RIV4 and cell-culture based inactivated influenza vaccine (ccIIV4) have not been compared to egg-based IIV4 in healthcare personnel, a population with frequent influenza vaccination that may blunt vaccine immune responses over time. We conducted a randomized trial among healthcare personnel (HCP) aged 18–64 years to compare humoral immune responses to ccIIV4 and RIV4 to IIV4. Methods: During the 2018–2019 season, participants were randomized to receive ccIIV4, RIV4, or IIV4 and had serum samples collected prevaccination, 1 and 6 months postvaccination. Serum samples were tested by hemagglutination inhibition (HI) for influenza A/H1N1, B/Yamagata, and B/Victoria and microneutralization (MN) for A/H3N2 against cell-grown vaccine reference viruses. Primary outcomes at 1 month were seroconversion rate (SCR), geometric mean titers (GMT), GMT ratio, and mean fold rise (MFR) in the intention-to-treat population. Results: In total, 727 participants were included (283 ccIIV4, 202 RIV4, and 242 IIV4). At 1 month, responses to ccIIV4 were similar to IIV4 by SCR, GMT, GMT ratio, and MFR. RIV4 induced higher SCRs, GMTs, and MFRs than IIV4 against A/H1N1, A/H3N2, and B/Yamagata. The GMT ratio of RIV4 to egg-based vaccines was 1.5 (95% confidence interval [CI] 1.2–1.9) for A/H1N1, 3.0 (95% CI: 2.4–3.7) for A/H3N2, 1.1 (95% CI: .9–1.4) for B/Yamagata, and 1.1 (95% CI: .9–1.3) for B/Victoria. At 6 months, ccIIV4 recipients had similar GMTs to IIV4, whereas RIV4 recipients had higher GMTs against A/H3N2 and B/Yamagata. Conclusions: RIV4 resulted in improved antibody responses by HI and MN compared to egg-based vaccines against 3 of 4 cell-grown vaccine strains 1 month postvaccination, suggesting a possible additional benefit from RIV4. Clinical Trials Registration: NCT03722589. Abstract : In this randomized trial among healthcare personnel comparing antibody responses to cell-culture based and recombinant influenza vaccines (RIV4) versus standard-dose egg-based vaccines, RIV4 recipients had higher antibody responses against 3 cell-grown vaccine strains suggesting a possible additional benefit from RIV4.